The crystal structure of N,N′-((nitroazanediyl)bis(methylene))diacetamide, C6H12O4N4 - Cong Chen; Ruxin Zhang; Shiyu Li; Lizhen Chen; Jianlong Wang (Zeitschrift für Kristallographie - New Crystal Structures)
C6H12O4N4, monoclinic, Cc (no. 9), a = 9.8171(4) Å, b = 16.1119(6) Å, c = 6.9125(5) Å, β = 121.443°, V = 932.81(9) Å3, Z = 4, Rgt(F) = 0.0346, wRref(F2) = 0.0894, T = 170 K.